Genome-Wide Identification and Expression Profile of the SNAT Gene Family in Tobacco (Nicotiana tabacum) - Zhang, Jiemei; Yao, Zhengping; Zhang, Renjun; Mou, Zongmin; Yin, Honghui; Xu, Tianyang; Zhao, Dake; Chen, Suiyun (Frontiers in Genetics, 2020)
Melatonin plays key roles in development and confers stress tolerance to plants. Serotonin N-acetyltransferase (SNAT) is either the enzyme involved in the last step or the penultimate enzyme of phytomelatonin biosynthesis. To date, SNAT genes have not been characterized in tobacco (Nicotiana tabacum), an economically important plant species. The sequence of the Acetyltransf_7 conserved domain was used as a query sequence, and 12 NtSNAT candidate genes were in turn identified in the genome of tobacco. These NtSNATs could be divided into two groups based on the phylogenetic tree. NtSNAT1 and NtSNAT2 clustered together with the other typical SNATs, but the other 10 NtSNATs separately clustered outside of the typical SNATs. These 10 NtSNATs have only motif 1, whereas representative SNATs, such as NtSNAT1 and NtSNAT2 or a SNAT from cyanobacteria, have five motifs. In addition, NtSNAT1 and NtSNAT2 are highly homologous to the characterized OsSNAT1, 62.95 and 71.36%, respectively; however, the homology between the other 10 NtSNAT genes and OsSNAT1 is low. Concomitantly, it is hypothesized that NtSNAT1 and NtSNAT2 are the homolog of SNATs, whereas the other 10 candidates could be considered NtSNAT-like genes. Furthermore, both Nicotiana tomentosiformis and Nicotiana sylvestris, two diploid ancestor species of N. tabacum, have two SNAT candidates; therefore, it is speculated that gene rearrangement or deletion during the process of genomic stabilization after whole-genome duplication or polyploidization led to the preservation of NtSNAT1 and NtSNAT2 during the evolution of tobacco from the ancestral diploid to the allotetraploid. NtSNAT and NtSNAT-like genes were differentially expressed in all organs under different stress conditions, indicating that these genes potentially associated with plant growth and development and stress resistance. Under different stress conditions, the expression of NtSNAT1 was significantly upregulated upon high-temperature and cadmium stresses, while the expression of NtSNAT2 did not significantly increase under any of the tested stress treatments. These results provide valuable information for elucidating the evolutionary relationship of SNAT genes in tobacco and genetic resources for improving tobacco production in the future.